The association between pharmaceutical innovation and both premature mortality and hospital utilization in Switzerland, 1996-2019 - Frank R. Lichtenberg (Swiss Journal of Economics and Statistics, 2022)
We analyze the association that pharmaceutical innovation had with premature mortality from all diseases in Switzerland during the period 1996-2018, and its association with hospital utilization for all diseases in Switzerland during the period 2002-2019. The analysis is performed by investigating whether the diseases that experienced more pharmaceutical innovation had larger subsequent declines in premature mortality and hospitalization. Pharmaceutical innovation is measured by the growth in the number of drugs used to treat a disease ever registered in Switzerland. Utilization of a chemical substance reaches a peak 9-12~years after it was first launched, and then declines. Our estimates indicate that the number of years of potential life lost before ages 85, 75, and 65 is significantly inversely related to the number of chemical substances ever registered 6-9, 3-9, and 0-9~years earlier, respectively. The new chemical substances that were registered during the period 1990-2011 are associated with reductions in the number of years of potential life lost before ages 85, 75, and 65 in 2018 of 257 thousand, 163 thousand, and 102 thousand, respectively. The number of hospital days is significantly inversely related to the number of chemical substances ever registered 8-10~years earlier. The new chemical substances that were registered during the period 1994-2010 are associated with reductions in the number of hospital days in 2019 of 2.07 million. Average length of inpatient hospital stays is significantly inversely related to the number of chemical substances ever registered 2-10~years earlier. The new chemical substances that were registered during the period 1999-2015 are associated with reductions in the average length of stays in 2019 of 0.4~days. Under the assumption that pharmaceutical innovation is exogenous with respect to premature mortality and hospitalization, and that it is uncorrelated with other potential determinants of health outcomes, if we ignore the reduction in hospital utilization associated with previous pharmaceutical innovation, a rough estimate of the cost per life-year before age 85 gained in 2018 is exteuro 14,310. However, about 85% of the 2018 expenditure on drugs registered during the period 1990-2011 may have been offset by the reduction in expenditure on inpatient curative and rehabilitative care. The net cost per life-year before age 85 gained in 2018 may therefore have been exteuro 2201.
Keywords: 330; Hospitalization; Innovation; Longevity; Prescription drugs; Switzerland